Existence and asymptotic properties of solutions for a nonlinear Schrödinger elliptic equation from geophysical fluid flows - Zhang, Xinguang; Jiang, J.; Wu, Y.; Cui, Y. (Elsevier, 2019)
In this paper, we study the existence and asymptotic behavior of radial solutions for a class of nonlinear Schrödinger elliptic equations on infinite domains describing the gyre of geophysical fluid flows. The existence theorem and asymptotic properties of radial positive solutions are established by using a new renormalization technique.